Strategi Komunikasi Human Capital BRI RO Semarang Pada Proses Rekrutmen BBAP - Rasyandra Aulia Narwastu; Liya Umaroh (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
The rapid development of technology and digital transformation has changed communication patterns in the banking sector, particularly in the dissemination of recruitment information and the management of human resources. These changes create communication challenges for banking institutions in attracting and managing qualified human resources, making effective communication strategies essential in recruitment activities. This study aims to analyze the communication strategies implemented by the Human Capital Division of Bank Rakyat Indonesia (BRI) Regional Office Semarang in the recruitment activities of the BBAP (BRILian Banking Associate Program). This research employs a qualitative descriptive method with a case study approach. The research subject is the Human Capital Division of BRI Regional Office Semarang. Data were collected through in-depth interviews, participatory observation, and documentation related to communication activities in the BBAP recruitment process. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the communication strategies applied. The results indicate that the Human Capital Division of BRI RO Semarang applies an integrated communication strategy by combining direct and digital communication approaches. Digital media such as social media and career websites are utilized to expand information reach, while direct communication is carried out through collaborative activities such as job fairs and internal coordination. These strategies support effective recruitment communication and the development of adaptive and high-quality human resources.